Media Game Edukasi Gakera pada Materi Kerajaan Nusantara - Meliana Putri Pramihapsari; Kurniana Bektiningsih (Universitas Pendidikan Ganesha, 2024)
Teachers still need to work on providing learning media, especially technology-based media. The impact of this is low student learning outcomes. Thus, this research aims to develop technology-based learning media for grade IV elementary school science and science lesson content on Nusantara Kingdom material to improve student learning outcomes. This research is research and development (R&D). The development model used is the ADDIE development model. The data collection methods were observation, tests, questionnaires, and interviews. The data collection instruments are questionnaires and test questions. The research subjects are media experts and learning material experts. The test subjects, namely in the small-scale trial, were 6 students, while on a large scale, there were 18 students. Data analysis techniques use descriptive qualitative, quantitative analysis, and inferential statistics. The results of the feasibility test for Gakera's educational game media products, assessed by a team of experts, obtained an average score of 90% from media experts, which was included in the very feasible category. Furthermore, the average feasibility score by material experts was obtained at 87.5% with very feasible criteria. Next, a t-test was obtained with a Sig value. (2-tailed) of 0.000 on a small scale and a large scale. The Gakera educational game media was feasible and practical to be applied in the learning process because it increased student motivation and learning outcomes.